Early Induction of Oxidative Stress in Mouse Model of Alzheimer Disease with Reduced Mitochondrial Superoxide Dismutase Activity - Lee, Hyun-Pil; Pancholi, Neel; Esposito, Luke; Previll, Laura A.; Wang, Xinglong; Zhu, Xiongwei; Smith, Mark A.; Lee, Hyoung-gon (PLOS ONE, 2012)
While oxidative stress has been linked to Alzheimer's disease, the underlying pathophysiological relationship is unclear. To examine this relationship, we induced oxidative stress through the genetic ablation of one copy of mitochondrial antioxidant superoxide dismutase 2 (Sod2) allele in mutant human amyloid precursor protein (hAPP) transgenic mice. The brains of young (5–7 months of age) and old (25–30 months of age) mice with the four genotypes, wild-type (Sod2+/+), hemizygous Sod2 (Sod2+/−), hAPP/wild-type (Sod2+/+), and hAPP/hemizygous (Sod2+/−) were examined to assess levels of oxidative stress markers 4-hydroxy-2-nonenal and heme oxygenase-1. Sod2 reduction in young hAPP mice resulted in significantly increased oxidative stress in the pyramidal neurons of the hippocampus. Interestingly, while differences resulting from hAPP expression or Sod2 reduction were not apparent in the neurons in old mice, oxidative stress was increased in astrocytes in old, but not young hAPP mice with either Sod2+/+ or Sod2+/−. Our study shows the specific changes in oxidative stress and the causal relationship with the pathological progression of these mice. These results suggest that the early neuronal susceptibility to oxidative stress in the hAPP/Sod2+/− mice may contribute to the pathological and behavioral changes seen in this animal model.